The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ani12141791
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Acute Nitrite Exposure on Physiological Stress Response, Oxidative Stress, Gill Tissue Morphology and Immune Response of Large Yellow Croaker (Larimichthys crocea)

Abstract: Nitrite is a common pollutant in aquaculture water, and nitrite toxicity that negatively affects aquatic species is common in aquaculture systems when the water quality is low. Therefore, the present research aimed to evaluate the effect of acute nitrite exposure on the hematological parameters, antioxidant enzymes, immune response, and gill morphology of large yellow croaker (Larimichthys crocea). The fish were randomly separated and exposed to four (i.e., 0, 29.36, 58.73, and 88.09 mg/L) nitrite concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Several of the enzymes selected in this study are usually regarded as indicators of the stress response [ 41 , 42 ]. The gills can be directly exposed to various environmental stimuli, such as hypoxia [ 43 ] and nitrite toxicity [ 44 ]; thus, the stress response may be stronger than that of other tissues. Accordingly, the results of the present study showed that LDH, SOD, GPT, and GOT activity was relatively higher in gill tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the enzymes selected in this study are usually regarded as indicators of the stress response [ 41 , 42 ]. The gills can be directly exposed to various environmental stimuli, such as hypoxia [ 43 ] and nitrite toxicity [ 44 ]; thus, the stress response may be stronger than that of other tissues. Accordingly, the results of the present study showed that LDH, SOD, GPT, and GOT activity was relatively higher in gill tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The data were expressed as the mean ± SD. According to the method of Xu et al [31], a two-way ANOVA (listed in Table 1) was used to analyze the independent and interactive effects of exposure time and nitrite concentration. If significant differences of interaction were found, Duncan's multiple range tests were used to determine the differences between means.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high nitrite levels in water depend on agricultural fertilizer use and untreated wastewater discharge [8]. Organisms living in nitritecontaminated aquatic environments can experience oxidative stress in gills and serum, negatively affecting the growth and development of aquatic organisms [34]. On the other hand, PO4 3--P in the water bodies of Soc Trang province fluctuated from 0.12±0.42 mg/L (dry season) to 0.16±0.34 mg/L (rainy season), 1.2-1.6 times higher than the Vietnamese standard.…”
Section: Surface Water Quality Based On National Surface Water Qualit...mentioning
confidence: 99%